2017
DOI: 10.1021/acssuschemeng.7b01616
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solutions of Surface-Active Ionic Liquids: Remarkable Alternative Solvents To Improve the Solubility of Triterpenic Acids and Their Extraction from Biomass

Abstract: Triterpenic acids (TTAs) are well known for their relevant biological properties and have been facing an increasing interest for nutraceutical and pharmaceutical applications. To overcome the concerns associated to the commonly used volatile organic solvents for their extraction from biomass, here we investigate the potential of aqueous solutions of ionic liquids (ILs) as alternative solvents. The solubility of ursolic acid (UA) was firstly determined in several aqueous solutions of ILs (hydrotropes or surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…For example, Domingues et al [11] have optimized the extraction of TTAs from E. globulus outer bark using supercritical CO 2 , under 200 bar, 40 • C and 5% ethanol, but with extraction yields 20% lower than those obtained with dichloromethane [12]. Ionic liquids have also been recently studied for the extraction of TTAs, achieving higher extraction yields when compared to conventional solvents [29]. This last study opened new perspectives to study alternative and tunable solvents for the extraction of TTAs from E. globulus outer bark, as ionic liquids but also deep eutectic solvents (DES) [30].…”
Section: Betulinic Acid Ursolic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Domingues et al [11] have optimized the extraction of TTAs from E. globulus outer bark using supercritical CO 2 , under 200 bar, 40 • C and 5% ethanol, but with extraction yields 20% lower than those obtained with dichloromethane [12]. Ionic liquids have also been recently studied for the extraction of TTAs, achieving higher extraction yields when compared to conventional solvents [29]. This last study opened new perspectives to study alternative and tunable solvents for the extraction of TTAs from E. globulus outer bark, as ionic liquids but also deep eutectic solvents (DES) [30].…”
Section: Betulinic Acid Ursolic Acidmentioning
confidence: 99%
“…The mobile phase consisted of 87% (v/v) methanol, and 13% (v/v) of an aqueous solution of 0.1% (v/v) TFA. Separations were conducted in isocratic mode, at a flow rate of 1 mL min −1 and with an injection volume of 10 µL [29]. The wavelength was set at 210 nm.…”
Section: Ursolic Acid Solubility Testsmentioning
confidence: 99%
“…Furthermore, it was recently demonstrated that they can also be used in the dissolution of more complex biomacromolecules, such as lignin [ 10 ]. Also worth noting, and similarly to ionic liquids [ 11 , 12 , 13 ], it was demonstrated that aqueous solutions of DES can perform better than the pure solvents [ 14 ], with inherent economic and process benefits. Finally, if benign or natural-based DES (the so called NADES) are used, these may be kept in the final formulations, in some cases also contributing to the improvement of the extracts biological properties [ 15 , 16 ], again with a close similarity to ILs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both cationic and anionic SAIL have been designed and investigated for their self‐assembly by changing the alkyl chain length, charged head group structure, functional groups, and counterions (Anouti et al, ; Baker et al, ; Blesic et al, , ; Galgano and El Seoud, ; García et al, ; Pillai et al, ; Rao et al, ; Šarac et al, ; Singh et al, ; Wang et al, ; Wang and Wang, ). The high tunability of IL opens up a broad range of applications for SAIL such as in micellar catalysis (Adam et al, ; Bica et al, ; Cognini et al, ) and in analytical chemistry and separation science (de Faria et al, ; Pino et al, ; Ressman et al, ). It was also demonstrated that some SAIL can be effective alternatives to the surfactants commonly used in enhanced oil recovery (EOR) processes with important advantages over the traditional surfactants and polymer‐flooding methods (Bera and Belhaj, ; Lago et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…* Claudia G. Adam cadam@conicet.gov.ar * Graciela G. Fortunato gfortuna@fiq.unl.edu.ar 2014; Šarac et al, 2017;Singh et al, 2016;Wang et al, 2008;Wang and Wang, 2014). The high tunability of IL opens up a broad range of applications for SAIL such as in micellar catalysis (Adam et al, 2017;Bica et al, 2012;Cognini et al, 2016) and in analytical chemistry and separation science (de Faria et al, 2017;Pino et al, 2012;Ressman et al, 2013). It was also demonstrated that some SAIL can be effective alternatives to the surfactants commonly used in enhanced oil recovery (EOR) processes with important advantages over the traditional surfactants and polymer-flooding methods (Bera and Belhaj, 2016;Lago et al, 2012;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%